Gestión de aceites lubricantes usados en el cantón el Guabo - Armijos López, Jennifer Dennis; Gaona Rueda, María Alexandra (Machala : Universidad Técnica de Machala., 2018)
El uso de aceites lubricantes se ha convertido en la actualidad en las mayores problemáticas a nivel mundial debido al impacto que estos ocasionan al ambiente por su inadecuada disposición final. En nuestro país la generación de desechos peligrosos como aceites lubricantes usados deben ser tratados y entregados a un gestor ambiental, quien se encarga de darle el correcto confinamiento, esto se encuentra estipulado en los acuerdos ministeriales 026, 061, mencionando los lineamientos a seguir, además de obtener la aprobación del Ministerio de Ambiente del Ecuador a través del departamento de Calidad Ambiental. El índice del parque automotor del cantón El Guabo ha crecido considerablemente desde el año 2010, actualmente cuenta con 11.356 vehículos aproximadamente, siendo los centros para mantenimiento como lubricadoras, mecánicas y lavadoras aquellas beneficiadas con este incremento considerable. El Cantón El Guabo, cuenta con 24 centros de servicio automotriz, considerando que 23 no cuentan con las condiciones básicas de infraestructura necesaria para funcionar como lubricadoras, mecánicas y lavadoras. Los centros de servicios automotriz del Cantón El Guabo, no cumple con la normativa ambiental vigente sobre el manejo de desechos peligrosos, es por esa razón que se propone un mecanismo para facilitar el proceso
The use of lubricating oils has currently become the main problems worldwide due to the impact they cause to the environment due to its inadequate final disposal. In our country, the generation of dangerous products such as lubricating oils, is due to the ministerial treatments 026, 061, and to the ministerial treatments to follow. to obtain the approval of the Ministry of Environment of Ecuador through the Department of Environmental Quality. The index of the car park of the city El Guabo has grown considerably since 2010, currently has approximately 11,356 vehicles, with maintenance centers such as lubricators, mechanics and washing machines benefiting from this considerable considerable. In city El Guabo, has 24 automotive service centers, considering that 23 does not have the basic infrastructure necessary to operate as lubricators, mechanics and washing machines. The automotive service centers of city El Guabo, do not comply with the current environmental regulations on the management of hazardous waste, it is for that reason that it is a mechanism to facilitate the process of regularization and once they can reject impacts to the environment. In addition to studying the amount of lubricating oils that enter and leave the automotive service centers in order to know where the surplus lubricant used and what is its final destination remains. The main problems detected in our research work on lubricating oils used in the city El Guabo were three, taking into account the classification of hazardous waste with medium severity, the other problems at the time of the incident, the regularization of the activity , spill of used oil direct to the ground with a high severity.
Keywords: DESECHO; AUTOMOTRIZ; LUBRICANTE; SERVICIO